BIMBINGAN ROHANI ISLAM UNTUK MEMBANTU PEMULIHAN PADA IBU YANG KECANDUAN NARKOBA - Karomah, Umi; Nurhikmah, Novita Sari Putri; Azizah, Nur (Prodi Bimbingan dan Konseling Islam Fakultas Dawah dan Komunikasi UIN Ar-Raniry, 2024)
This research discusses the role and function of implementing Islamic spiritual guidance in institutional settings, such as the National Narcotics Agency, in supporting the recovery process for drug addicts. In the sense that Islamic spiritual guidance is made for addicts, namely so that they can be aware and get closer to the creator by providing religious material or spiritual coaching by a clergyman. In this study, the method used is a qualitative type with a case study approach. The subject under study is a mother, and data collection techniques through interviews and observation. Meanwhile, the data analysis uses the results of conducting interviews plus a literature review. The results of this study indicate that applying Islamic spiritual guidance in these institutions can be an alternative to helping drug addicts to change their maladaptive habits. Therefore, this journal directs that more and more institutions hold Islamic spiritual guidance programs to help others.